2008
DOI: 10.1590/s0102-05362008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin residues applied in different formulations in staked cucumber and the actions of insecticides on the pickleworm control

Abstract: Pesticide residues, especially in vegetables and fruits, are a reason for concern with respect to the health of consumers and workers that need to return to areas that have been treated with these agrochemicals. The objectives of this experiment were to (a) study the behavior of deltamethrin residues from different formulations on cucumber fruits; and (b) correlate insecticide contents in the fruits with pickleworm control. Treatments were as follows: (a) control; (b) three 30 mL applications of deltamethrin 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Since, it was found that deltamethrin was commonly used (Dhore, 2016;Sali, 2016) on capsicum in the region; the present study was conducted to analyse degradation variations of deltamethrin in polyhouse and eld grown capsicum. Deltamethrin is a pyrethroid ester insecticide, found effective against sucking insect pests on glasshouse cucumbers, tomatoes, peppers and ornamentals (Baptista et al, 2008) besides managing numerous insect pests of eld crops with low application rates (Deo et al, 1991). Deltamethrin is not recommended or label claimed in capsicum under recommended insecticides list of Central Insecticide Board and Registration Committee (CIB and RC) of the Government of India.…”
Section: Introductionmentioning
confidence: 99%
“…Since, it was found that deltamethrin was commonly used (Dhore, 2016;Sali, 2016) on capsicum in the region; the present study was conducted to analyse degradation variations of deltamethrin in polyhouse and eld grown capsicum. Deltamethrin is a pyrethroid ester insecticide, found effective against sucking insect pests on glasshouse cucumbers, tomatoes, peppers and ornamentals (Baptista et al, 2008) besides managing numerous insect pests of eld crops with low application rates (Deo et al, 1991). Deltamethrin is not recommended or label claimed in capsicum under recommended insecticides list of Central Insecticide Board and Registration Committee (CIB and RC) of the Government of India.…”
Section: Introductionmentioning
confidence: 99%